Diffusion-weighted imaging and dynamic contrast-enhanced MRI of experimental breast cancer bone metastases: a correlation study with histology - Merz, Maximilian (European journal of radiology, 2015)
To validate imaging parameters from diffusion-weighted imaging and dynamic contrast-enhanced MRI with immunohistology and to non-invasively assess microstructure of experimental breast cancer bone metastases. Animals bearing breast cancer bone metastases were imaged in a clinical 1.5T MRI scanner. HASTE sequences were performed to calculate apparent diffusion coefficients. Saturation recovery turbo FLASH sequences were conducted while infusing 0.1mmol/l Gd-DTPA for dynamic contrast-enhanced MRI to quantify parameters amplitude A and exchange rate constant kep. After imaging, bone metastases were analyzed immunohistologically. We found correlations of the apparent diffusion coefficients from diffusion-weighted imaging with tumor cellularity as assessed with cell nuclei staining. Histological vessel maturity was correlated negatively with parameters A and kep from dynamic contrast-enhanced MRI. Tumor size correlated inversely with cell density and vessel permeability as well as positively with mean vessel calibers. Parameters from the rim of bone metastases differed significantly from values of the center. In vivo diffusion-weighted imaging and dynamic contrast-enhanced MRI in experimental bone metastases provide information about tumor cellularity and vascularity and correlate well with immunohistology.
Gesehen am 21.07.2017